Controversies in orbital reconstruction—I. Defect-driven orbital reconstruction: A systematic review. Issue 3 (March 2015) - Dubois, L.; Steenen, S.A.; Gooris, P.J.J.; Mourits, M.P.; Becking, A.G.
Abstract In the 1980s, computed tomography was introduced as an imaging modality for diagnosing orbital fractures. Since then, new light has been shed on the field of orbital fracture management. Currently, most surgeons are likely to repair orbital fractures based on clinical findings and particularly on data obtained from computed tomography scans. However, an important but unresolved issue is the fracture size, which dictates the extent and type of reconstruction. In other fields of trauma surgery, an increasing body of evidence is stressing the importance of complexity-based treatment models. The aim of this study was to systematically review all articles on orbital reconstruction, with a focus on the indication for surgery and the defect size and location, in order to identify the reconstruction methods that show the best results for the different types of orbital fractures.